2019
DOI: 10.1093/mnras/stz3048
|View full text |Cite
|
Sign up to set email alerts
|

The GALAH survey: temporal chemical enrichment of the galactic disc

Abstract: We present isochrone ages and initial bulk metallicities ([Fe/H] bulk , by accounting for diffusion) of 163,722 stars from the GALAH Data Release 2, mainly composed of main sequence turn-off stars and subgiants (7000K > T eff > 4000K and logg > 3 dex). The local age-metallicity relationship (AMR) is nearly flat but with significant scatter at all ages; the scatter is even higher when considering the observed surface abundances. After correcting for selection effects, the AMR appear to have intrinsic structures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 121 publications
(153 reference statements)
0
18
0
Order By: Relevance
“…The difference in Eu abundance ratios between the low-α and high-α populations could be understood if there is a delay in r-process enrichments; the long star formation timescale of the low-α population might have allowed the delayed r-process enrichments to contribute to the chemical evolution. The delay time of r-process events is, however, still under debate (Hotokezaka et al 2018;Côté et al 2019;Lin et al 2020;Skúladóttir & Salvadori 2020). While neutron star mergers, which are associated with short gamma-ray bursts (GRBs), are promising r-process sites, these studies suggested that there should be more r-process production events in the…”
Section: Constraints From Abundancesmentioning
confidence: 99%
“…The difference in Eu abundance ratios between the low-α and high-α populations could be understood if there is a delay in r-process enrichments; the long star formation timescale of the low-α population might have allowed the delayed r-process enrichments to contribute to the chemical evolution. The delay time of r-process events is, however, still under debate (Hotokezaka et al 2018;Côté et al 2019;Lin et al 2020;Skúladóttir & Salvadori 2020). While neutron star mergers, which are associated with short gamma-ray bursts (GRBs), are promising r-process sites, these studies suggested that there should be more r-process production events in the…”
Section: Constraints From Abundancesmentioning
confidence: 99%
“…While stars are thought to be more metal-rich on average at later formation epochs, the age-metallicity relationship in the solar neighborhood appears to be relatively flat beyond an initial early enrichment phase (e.g., Lin et al 2020;Haywood et al 2019), inferring that a single non-age-dependent metallicity distribution will be sufficient to represent the solar neighborhood. Re-gardless of whether metallicity is truly constant with time, it may not influence our detection of young stars, since the nearly age-independent photometry of mainsequence stars means that the age will weigh minimally on the photometry of these stars, regardless of metallicity.…”
Section: Metallicitymentioning
confidence: 99%
“…They showed that a number of elements show abundance trends with age and much of the scatter for a given age can be attributed to metallicity. Lin et al (2020), using data from GALAH DR2, also explored trends with both age and metallicity.…”
Section: Introductionmentioning
confidence: 99%